Rethinking Jacques Derrida’s Deconstruction and its Relevance to the Study of Islam - Abdul Fattah (Universitas Islam Negeri Mataram, 2019)
This article examines Jacques Derrida’s concept of deconstruction and its implementation in the context of contemporary Islamic studies. Philosophically, the status of texts should not be regarded merely as writing because the meaning goes beyond the lexicogrammatical boundaries. Hence, scrutinizing ways to unveil hidden meanings possibly entail subjective or partial values embedded in the texts, particularly religious texts pertinent to Islamic civilization (turāth). Based on the philosophical analysis of the Derrida’s work, this study shows that there are at least two points of the relevance of the Derrida's philosophical thought to deconstruct the turāth and the Western domination in Muslim society. First, it is a useful device to criticise and deconstruct religious thoughts and texts, which are, to some extent, still dominant and considered sacred. These cover a wide range of Islamic texts that build Islamic civilization, from mysticism, law to theology. The second dimension is dismantling the context (today Muslim civilization) through decentralization of the Western hegemony and promotion of Occidentalism, a way of seeing the West from the East.